EXPERIMENTAL RESPONSE TO DENSITY LEVELS IN THE DEVELOPMENT OF TADPOLES AND FROGLETS OF Boana pulchella (ANURA: HYLIDAE) - Maneyro, Raúl; Francescoli, Gabriel (Boletín de la Sociedad Zoológica del Uruguay, 2019)
Density has been proposed as a factor that could determinate larval growth in anurans. We studied such effects on Boana pulchella. After hatching, we reared the tadpoles during 90 days and 93 tadpoles with similar size and developmental stages were chosen. We placed them in 800 cm3 cans with declorified water at five densities (1, 2, 4, 8 and 16 individuals/can) with three replicates for each treatment. In all the cans the feeding was ad libitum, and they were maintained until the end of the Gosner’s developmental stage 41. Each time that a tadpole was extracted, a proportional water volume was too, in order to maintain constant densities. We found significant differences among treatments for froglets’ length, mandibular width and mass, while these differences were not significant for metamorphic time. Since the tadpoles were feeding ad libitum an explanation by competitive trophic interactions for that significant differences could be discarded. These differences could be evidence that density has significant effects.